The Status of Parthenium Hysterophorus and its Potential Management - Bhowmik, P. C.; Sarkar, D.; Yaduraju, N. T. (Ecoprint: An International Journal of Ecology, 2016)
Available with fulltext. Ecoprint An International Journal of Ecology Vol. 14, 2007 Page: 1-17 Uploaded date: 31 May, 2011